Road warriors : foreign fighters in the armies of Jihad - Byman, Daniel, 1967- (New York, NY, United States of America : Oxford University Press, 2019)
"Road Warriors" is a history of the modern jihadist movement, detailing the lives and struggles of foreigners who left their homes to wage jihad in another country. Some died there, while others became professional fighters, going from one war to the next. Still others sought to return home or to the United States and Europe, some to peaceful retirement but a deadly few to conduct terrorist attacks. This book shows how governments have tried to fight the group and assesses what worked and what needs to be done.
Why do foreign fighters matter? -- The prophet : Abdullah Azzam and the anti-Soviet jihad in -- Barbaros: the red beard -- The trainer : Ali Mohammad and Afghanistan in the 1990s -- Chechnya and the sword of Islam -- Hubris and nemesis : the Chechen foreign fighters overreach -- The slaughterer : Abu-Musab al-Zarqawi and ascendant Iraqi Jihad (2003-2006) -- The dreamer : Abu Ayyub al-Masri and the self-destruction of the Iraqi Jihad -- The gadfly : Omar Hammami -- John the Beatle and the Syrian Civil War -- The facilitator : Amer Azizi and the rise of Jihadist terrorism in Europe -- America squares off against the Legion -- How to stop foreign fighters.
Includes bibliographical references and index.
Keywords: Terrorists -- Recruiting; Terrorism -- Prevention; Terrorism -- Religious aspects -- Islam; Jihad